THE EFFECT OF VILLAGE FUNDS AND SPECIAL AUTONOMY FUNDS ON POVERTY IN WEST PAPUA PROVINCE - Silaban, Maman Kurniawan Syahputra; Nuryartono, Nunung; Putri, Eka Intan Kumala (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: Poverty is still a significant obstacle to development in Indonesia. To overcome this, fiscal policy through Village Funds is provided to all regions of Indonesia, including West Papua Province. In addition to Village Funds, West Papua Province had received Special Autonomy Funds from the Indonesian Government long before as a manifestation of asymmetric fiscal policy. However, the poverty conditions in West Papua Province have yet to be resolved. This study discusses the extent to which village funds and special autonomy funds affect poverty in West Papua Province. Methods: This study uses a quantitative approach with descriptive and inferential analysis methods through panel data regression. The secondary data were collected from 12 regencies during the period 2015-2024. The poverty indicators used are the poverty headcount ratio (percentage) and the poverty headcount (in thousands of people). Results: The study results show that village funds in the current year and the previous year (t-1) significantly improve poverty indicators, while Special Autonomy Funds do not. Other variables, such as the Human Development Index (HDI), significantly reduce poverty levels, while the Gini Ratio significantly worsens the poverty headcount. Conclusion and suggestion: Village Funds have been statistically proven to reduce poverty outcomes in West Papua Province, while Special Autonomy Funds have not shown a significant effect. This finding underlines the importance of a comprehensive evaluation of the management of Special Autonomy Funds. In the future, development efforts should focus on enhancing the quality of human resources and making genuine efforts to reduce income inequality.